Metal worker’s lung; spatial association with Mycobacterium avium - Moffatt,MF; Cullinan,P; James,PL; Cannon,J; Barber,C; Crawford,L; Hughes,H; Jones,M; Szram,J; Cowman,S; Cookson,WOC (Thorax, 2017)
Background Outbreaks of hypersensitivity pneumonitis(HP) are not uncommon in workplaces where metalworking fluid (MWF) is used to facilitate metal turning.Inhalation of microbe-contaminated MWF has beenassumed to be the cause, but previous investigationshave failed to establish a spatial relationship between acontaminated source and an outbreak.Objectives After an outbreak of five cases of HP ina UK factory, we carried out blinded, molecular-basedmicrobiological investigation of MWF samples in orderto identify potential links between specific microbial taxaand machines in the outbreak zone.Methods Custom-quantitative PCR assays, microscopyand phylogenetic analyses were performed on blindedMWF samples to quantify microbial burden and identifypotential aetiological agents of HP in metal workers.Measurements and main results MWF frommachines fed by a central sump, but not those with anisolated supply, was contaminated by mycobacteria. Thefactory sump and a single linked machine at the centre ofthe outbreak zone, known to be the workstation of theindex cases, had very high levels of detectable organisms.Phylogenetic placement of mycobacterial taxonomicmarker genes generated from these samples indicatedthat the contaminating organisms were closely related toMycobacterium avium.Conclusions We describe, for the first time, a closespatial relationship between the abundance of amycobacterium-like organism, most probably M. avium,and a localised outbreak of MWF-associated HP.The further development of sequence-based analytictechniques should assist in the prevention of thisimportant occupational disease.